Personal Watches in Warsaw, 1890–1914: Social Meanings - Brzostek, Błażej (Acta Poloniae Historica, 2025)
The article discusses the phenomenon of personal watches in the Kingdom of Poland at the turn of the twentieth century. These lands can be considered doubly peripheral: both in terms of power over official time, which was exercised by the administration of the Russian partition (controlled from a centre in the East), and in terms of production of timepieces, which were imported from abroad (produced in the West). The importation of watches, mainly Swiss, was associated with various local practices (advertising campaigns, fabrication of dials with the names of local watchmakers, etc.), and above all, it created a spectrum of attitudes and symbols in the “theatre of everyday life”. The watch was a marker of gender, a symbol of social and professional status, power, and political attitudes; it signified historical memory and loyalty to superiors.